Cadaveric Investigation on Radial Nerve Strain Using Different Posterior Surgical Exposures for Extraarticular Distal Humeral ORIF: Merits of Nerve Decompression Through a Lateral Paratricipital Exposure. Issue 2 (February 2015) - Voigt, Clifford; Illical, Emmanuel; Goyal, Kanu S.; Farrell, Dana J.; Van Eck, Carola F.; Tarkin, Ivan S.
Abstract : Objective: To determine whether the type of posterior surgical approach for distal humeral fracture open reduction and internal fixation influenced radial nerve strain during simulated operative retraction in a cadaveric model. Methods: Three different posterior surgical exposures: triceps splitting, lateral paratricipital, and paratricipital with release of the lateral intermuscular septum were used. Radial nerve strain was measured using a microDVRT, while traction was applied with a digital force gauge at forces 0.1–0.3 kg. Results: The lateral paratricipital with nerve decompression was superior to both the triceps splitting approach ( P < 0.048) and paratricipital method without decompression ( P < 0.036). There was no significant difference between the triceps splitting method and paratricipital exposure without intermuscular septum release. Conclusions: Radial nerve decompression through release of the lateral intermuscular septum through a lateral paratricipital exposure ideally decreases nerve strain during humeral open reduction and internal fixation in our cadaveric model.